Aparición tardía de premolares supernumerarios. Revisión de literatura y presentación de casos - Hernandez, Jesus A.; Soto, Libia (Revista Estomatología, 2004)
The late formation of supernumerary premolars is more frequent than has been considered. Their prevalence is about 8 to 9% of all the supernumerary teeth; 75% of these teeth are impacted, without eruptional possibilities and generally remain asymptomatic. The study review the evidence about supernumerary teeth and also presence of supernumerary premolars. Four cases late presence of supernumerary premolars are presented with radiographic support.